Professionalism of Islamic spiritual guide - Wangsanata, Susana Aditiya; Supriyono, Widodo; Murtadho, Ali (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2020)
Purpose - The aim of this research was to recognize radically (deeply) the professionalism of Islamic spiritual guides.Method - This research used descriptive qualitative with the determination of informants using the model of snowball. The data analysis in this study used Creswell's theory of analysis ranging from data reduction, display, and to conclutions.Result - The results of this study indicate that a professional Islamic spiritual guide needs to meet three indicators in order to carry out counseling process optimally. The indicators of professionalism are relevant educational qualifications, expertise or qualified credibility, and finally the presence of payment commensurate with the quality of work. Meanwhile, the professionalism of Islamic spiritual guidance services is to pay attention to the time and material given to counselees so that they can display or provide Islamic spiritual guidance services professionally.Implications - The implication of this research is to improve performance professionally by absorbing the experts or specialists in the field of Islamic spiritual guidance.Originality - The originality of this study is that it is the first research model to apply the correlation research method with the LESKAP pattern.